Legal Education about Marriage of Women without Divorce Certificate and Previously Unregistered Marriage - Imam Sujono (International Journal of Law Society Services, 2022)
Marriage is a contract that justifies a man and a woman, with a marriage contract to build a happy and prosperous family. The marriage process has been regulated in Law Number 1 of 1974 that every marriage must be carried out according to religious provisions and must be recorded. The purpose of this study is to find out how the marriage process for women who were previously married without being recorded and divorced outside the Religious Court so that they do not have a divorce certificate. This study uses a normative juridical method. The results showed that for women whose marriages were not recorded and divorced outside the Religious Courts so that they did not have a divorce certificate, to enter into a new marriage the woman had to file a marriage isbath for divorce.